Implementação do Service Level Agreement no setor de pós-vendas no mercado peruano - Lebens, Alisson (My University, 2019)
Due to the constant growth in the service sector, according to Silva (2013), the companies have been preparing for the new scenario that is to come. This paper focuses mainly on the implementation of the Service Level Agreement (SLA), showing its importance. It presents the models and processes for the implementation of this service in a company from Caxias do Sul, in the Post-Sales sector, in the foreign market. It explains facts and ways it should be used, following the steps of authors quoted in the text. Using an exploratory case study methodology with a qualitative approach, it analyzed and sought to meet the needs of the client, aiming mainly to reach a satisfactory deadline. After verifying the implementation, it may be concluded that with a new process or new service for the Peruvian representative, it was possible to obtain better delivery times, making customer service faster and being able to have reliability again with its main targets in the market.(sic)
Devido ao crescimento constante no setor de serviços, segundo Silva (2013), as empresas vêm se preparando para o novo cenário que está por vir. Este presente trabalho tem como foco principal a implementação do Service Level Agreement (SLA), mostrando sua importância. Apresenta os modelos e processos para a implementação desse serviço em uma empresa de Caxias do Sul, no setor de Pós-Vendas, no mercado externo. Explica fatos e modos que se deve utilizar, seguindo passos de autores citados no texto. Usando uma metodologia de estudo de caso exploratória com abordagem qualitativa, analisou e buscou atender as necessidades do cliente, visando principalmente alcançar um prazo satisfatório. Após a verificação de implementação, pode-se concluir que com um novo processo ou novo serviço para o representante peruano, foi possível obter melhores prazos de entrega, agilizando o atendimento ao cliente, podendo ter confiabilidade novamente com seus principais alvos no mercado.(sic)
Keywords: Vendas - Peru; Comércio eletrônico